23 Utility Of Microcirculation Analysis in a Paediatric Animal Model of Hypovolemic Shock. (October 2012) - Gonzalez, R; Urbano, J; Lopez, J; Solana, MJ; García, A; Botran, M; López-Herce, J
Abstract : Background and aims: Evaluation of tisular perfusion is very important in critically ill patients. Several techniques are used to assess tisular blood flow. Most of them are invasive and non accurate. Sidestream dark field imaging is proposed to be a useful non-invasive method to evaluate microcirculation. Methods: Prospective, observational study in 17 two month-old piglets (8.6±1.1kg). Following mechanical ventilation, hypovolemic shock was induced by controlled 30 ml/kg bleed. 5 video sequences were recorded in each pig at basal time, during shock, and after fluid resuscitation using Microscan Microvision® device. Recorded video sequences were analysed later. Microcirculation was assessed determining perfused vessel density (PVD), microvascular flow index (MFI) and heterogeneity index (HI). Automated vascular analysis (AVA®) software was used to analyze the sequences. Results: Before bleed median values for PVD (13.6/mm3 ±2.4) and MFI (2.75±0.22) where higher and HI (0.21±0.14) was lower than during shock (12.4/mm3±1.4, 1.97±0.43 and 0.58±0.36 respectively) (p<0.05). After fluid resuscitation PVD and MFI median values increased (13.69/mm3±1.56 and 2.63±0.26 respectively) and HI decreased (0.32±0.22) (p<0.05). Conclusions: Lower vessel density and slower microvascular blood flow and higher flow heterogeneity occurred during shock. Computerized microcirculation analysis using sidestream dark field was able to distinguish between basal condition and hypovolemic shock and between hypovolemic shock and after fluid resuscitation.